(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2018)
Public diplomacy is used as an effort to engage and persuade foreign publics, an important factor in a foreign policy to improve the image and position of one country. The objectives of one country’s foreign policy can be obtained by dealing directly with the people of foreign countries. Today, in the information age, under the power of the media of causing an effect in indirect or intangible ways, new public diplomacy is implemented as an modern instrument and techniques of communication, a shift in diplomatic practices to engage with foreign publics and move away form one-way information flows toward dialogue and engagement. Therefore, a new media landscape challenge traditional foreign ministry “gatekeeper” structures, foreign ministry of foreign affairs can no longer being a dominant factor in communicating foreign policy. It requires a new away practice to being carried out with new media, new technologies to elucidate foreign policy to a range of non-governmental international actors, evaluate the influence of these communicative efforts. The paper will clarify the old and new theoretical framework of public diplomacy, the role and power of public diplomacy in foreign policy, the power of the media in the 21st century which influence the new public diplomacy practices of one country in general and the United States government in specific, covering national policy, current affairs, current activities. From these analyses, the paper will be concluded the new way for Vietnam Ministry of Foreign Affairs to implement its public diplomacy in the new era of media age.